Peran Pasraman Sebagai Lembaga Pendidikan Keagaman Hindu Dalam Pemertahanan Bahasa Bali di Kabupaten Lombok Barat - Desak Made Yoniartini; Mahsun; Burhanudin (Jayapangus Press, 2022)
Language is a means of communication, and it is also as an introduction to culture; therefore, it is essential for a community to maintain its regional language. The Balinese regional language is one of the languages ​​which still exists today; however, there is concern that the Balinese language (especially those which are outside Bali island) will no longer be able to survive due to the use of local languages, Indonesian and foreign languages in the future, especially used in educational institutions. In addition to formal educational institutions, the maintenance of the language can also be applied in Hindu religious education institutions such as pasraman. Pasraman is considered to have a crucial role of Balinese language preservation in non-formal educational institutions, particularly for children (bala) and youths (yowana). This study aimed to examine the role of pasraman in preserving Balinese language (oral and written) in West Lombok Regency. This study used a descriptive qualitative approach and the data collection methods used were the speaking and the listening method. The results of this study indicated that pasraman as a non-formal Hindu religious education institution had a very important role in the Balinese language maintenance. The preservation of the Balinese language in the pasraman consisted of two areas, namely the maintenance of written and spoken language. The maintenance of the former was conducted by teaching Balinese script (introduction to a writing system of Balinese script, writing Balinese script and reading Balinese script), while preservation of the latter was conducted by language interaction between acarya and brahmacari and interaction between fellow brahmacari uttering Balinese language in the pasraman environment during both the teaching learning process and after-school activities.